(untitled) (RIAF. International Journal of Physical Activity, 2024)
This research was conducted at the Cantonal League of Durán with the objective of designing a program of specific exercises to improve the technical fundamentals of passing and shooting in soccer. The aim is to help soccer players enhance their technical skills, become more effective in passing and shooting techniques, and achieve their maximum athletic performance in professional soccer. The methodology employed in this study is field-based, descriptive in nature, and utilizes a mixed-methods approach. To develop this research, various techniques and instruments were used for the collection of essential information, such as interviews with the head of the Cantonal League and an observation guide directed at two coaches focusing on the training process of the under-15 soccer category of the Cantonal League of Durán. This guide was also applied to the 16 soccer players for their respective evaluation of the technical fundamentals of passing and shooting in soccer. The results revealed difficulties in the use of methodological strategies, a low level of instruction among coaches, and shortcomings in the players’ passing and shooting techniques. Consequently, the study proposes the design of a program of specific exercises aimed at improving the technical fundamentals of passing and shooting in soccer. This program seeks to enhance the technical performance and overall athletic outcomes of the soccer players.